Praktik Pembayaran Zakat Dikalangan Nelayan Kecamatan Koto Kampar Hulu Kabupaten Kampar (Perspektif Hukum Islam) - Mustafid Mustafid (Institut Agama Islam Negeri Palopo, 2022)
According to Islamic law, this study examines the practice of paying Zakat among fishermen in Koto Kampar Hulu District, Kampar Regency. This article is field research using a qualitative approach that aims to explain the phenomenon of zakat payments to fishermen in Koto Kampar Hulu District from the perspective of Islamic Law. The data collection technique author uses observation, interviews, and documentation, while the data analysis technique uses descriptive qualitative. There are three findings in this study, namely: First: the objectivity of zakat objects in Koto Kampar upstream are plantations/agriculture, livestock, civil servants, and fishermen. Second: the payment of zakat on fishermen made by the fishing community is by issuing money to orphans, the poor, mosques, and MDA, with an unspecified amount, they give according to their income, they spend around Rp. 35,000-50,000 every week. Third: while it is seen from Islamic law that issuing zakat, must be by existing rules, then the zakat of fishermen is qiyased to trade zakat which is issued 2.5%, but local fishermen never issue it according to the rules. However, they are not people who are reluctant to pay zakat, they issue it according to the knowledge they have.